Comparison of emergency department time performance between a Canadian and an Australian academic tertiary hospital. (27th February 2019) - Cheng, Ivy; Taylor, David; Schull, Michael J; Zwarenstein, Merrick; Kiss, Alex; Castren, Maaret; Brommels, Mats; Yeoh, Michael; Kerr, Fergus
Abstract: Objective: To compare performance and factors predicting failure to reach Ontario and Australian government time targets between a Canadian (Sunnybrook Hospital) and an Australian (Austin Health) academic tertiary‐level hospitals in 2012, and to assess for change of factors and performance in 2016 between the same hospitals. Methods: This was a retrospective, observational study of patient administrative data in two calendar years. The main outcome measure was reaching Ontario and Australian ED time targets for admissions, high and low urgency discharges. Secondary outcomes were factors predicting failure to reach these targets. Results: Between 2012 and 2016, Sunnybrook and Austin experienced increased patient volume of 10.2% and 19.2%, respectively. Bed capacity decreased at Sunnybrook (−10.8%) but increased at the Austin (+30.3%). For both years, Austin failed to achieve the Australian time target, but succeeded for all Ontario targets except for low urgency discharges. Sunnybrook failed all targets irrespective of year. The top factors for failing Ontario ED length‐of‐stay targets for both hospitals in 2012 and 2016 were bed request greater than 6 h, access block greater than 1 h, use of cross‐sectional imaging, consultation and waiting for the emergency physician greater than 2 h. Conclusion: Austin outperformed Sunnybrook for Ontario and Australian government time targets. Both hospitals failed the Australian targets. Factors predicting failure to achieve targets were different between hospitals, but were mainly clinical resources. Sunnybrook focussed on increasing human resources. Austin focussed on increasing human resources, observation unit and hospital beds. Intrinsic hospital characteristics and infrastructure influenced target success.